Oral Vaccination with Salmonella enterica as a Cruzipain-DNA Delivery System Confers Protective Immunity against Trypanosoma cruzi - Cazorla, Silvia Ines (2008)
To stimulate both local and systemic immune responses against Trypanosoma cruzi, Salmonella enterica serovar Typhimurium aroA was exploited as DNA delivery system for cruzipain (SCz). In a murine model we compared SCz alone (GI) or co-administered with Salmonella carrying a plasmid encoding GM-CSF (GII), as well as protocols in which SCz priming was followed by boosting with recombinant cruzipain (rCz) add-mixed with either CpG-ODN (GIII) or MALP-2 (GIV). The results showed that protocols including four oral dosis of SCz (GI), elicited mainly a mucosal response characterized by IgA secretion and proliferation of GALT cells, with weak systemic responses. In contrast, the protocol including boost with rCz+CpG (GIII) triggered stronger systemic responses in terms of Cz-specific serum IgG titers, splenocytes proliferation and INF-ã secretion, and delayed type hypersensitivity response. Trypomastigote challenge of vaccinated mice resulted in significant lower levels of parasitemia respect to controls. Protection was abolished by depletion of either CD4+ or CD8+ T cells. Parasite control was also evident from the reduction of tissue damage, as revealed by histopathologic studies and serum levels of enzymes which are markers of muscle injury in chronic Chagas disease (i.e., creatine kinase, aspartate aminotransferase and lactate dehydrogenase). Enhanced release of IFN-ã and IL-2 was observed in GI and GII upon re-stimulation of splenocytes on the non-parasitic phase of infection. Our results indicate that Salmonella-mediated delivery of Cz-DNA by itself promotes the elicitation of an immune response that controls T. cruzi infection, thereby reducing parasite loads and subsequent damage to muscle tissues.